Effect of Intravitreal Antibiotic Injections on Culture-Negative Keratitis-Induced Endophthalmitis. Issue 6 (November 2020) - Sim, Ha Eun; Kang, Min-Ji; Kim, Jae-Suk; Hwang, Je-Hyung
Abstract : Background: This study aimed to evaluate treatment outcomes of culture-negative keratitis-induced endophthalmitis (CNKE). Methods: We reviewed the medical records of 13 patients with CNKE, who underwent treatment from January 2011 to December 2017. All patients were referred from the emergency department or outpatient departments of local clinics. Outcome evaluation included the assessment of visual acuity and any need for evisceration/enucleation. Results: Thirteen eyes of 13 patients were included in this study. The mean age of the patients was 75.0 ± 13.3 years. All patients had used antibiotic eye drops before the initial visit. Visual acuity values at the initial visit ranged from no light perception to 2/100; final visual acuity values ranged from no light perception to 2/100. All patients underwent a vitreous tap and intravitreal ceftazidime/vancomycin injection. Two eyes underwent evisceration after intravitreal injection. Conclusions: Intravitreal antibiotic injections demonstrated favorable results for the treatment of patients with CNKE.